Project-based digital portfolio: Biology assessment and learning innovation to improve student competency - Gusfarenie, Dwi; Nuraida, Nining; Suraida, Suraida (Indonesian Research Journal in Education |IRJE|, 2026)
This study aims to develop and evaluate the effectiveness of a project-based digital portfolio, BioPorta, as an assessment and learning medium in the Medicinal Plants course for biology students. The research employed a research and development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The product was validated by media and material experts, achieving high validity scores of 86.06% and 94%, respectively. Practical testing showed positive results, with scores of 90% from lecturers, 77.06% from small group trials, and 86.18% from field tests. The effectiveness test using N-gain analysis indicated a significant improvement in student learning outcomes, with a score of 0.805 in the experimental class compared to 0.225 in the control class. These findings demonstrate that BioPorta is a valid, practical, and effective tool for enhancing student competence, engagement, and learning outcomes through project-based digital learning.